PERFORMANCE OF EMPLOYEES IN TOURIST SERVICES ATTHE WEST SUMATERA PARK, TAMAN MINI INDONESIA INDAH - Priyanto, Priyanto (UI Scholars Hub, 2022)
This study aims to measure the performance of tour guides serving visitors and identify the obstacles that exist in the implementation of tour guide activities at the TMII West Sumatra Pavilion. The research method used is descriptive qualitative by means of interviews. observation, and literature study. The results show that the performance of the tour guide in serving visitors is still lacking in terms of discipline, appearance and suitability of working hours, so it can be concluded that the performance of the tour guide does not meet the requirements in the context of excellent service. The unavailability of local tour guides who master foreign languages, making foreign visitors who are not accompanied by a tour leader or tour guide can only enjoy the existing art props without a detailed explanation by a tour guide, and Tour Guides at the West Sumatra Pavilion, the attention, attitude, and action given to visitors are still not optimal. This research contributes practically to the service of tour guides at the TMII West Sumatra Park.